2020
DOI: 10.2319/070719-457.1
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of available sites for palatal orthodontic mini-implants through cone-beam computed tomography

Abstract: Objective To measure the palatal thickness of both hard and soft tissues and to determine safe regions for the placement of mini-implants. The influences of sex and age on palatal thickness were also examined. Materials and Methods Cone-beam computed tomography images of 30 patients (12 males, 18 females), including 15 adults and 15 adolescents, were used in this study. The thicknesses of palatal hard tissue, soft tissue, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 23 publications
0
23
0
4
Order By: Relevance
“…Because male and female patients have different growth patterns, the patient’s age and sex are important factors for determining the optimal implant placement site. Although several studies 8 , 9 have evaluated the hard tissue thickness of the palate, few have assessed the thickness of the soft tissue in the median and paramedian regions of the palate or investigated the influences of age and sex in terms of mini-implant insertion in these regions. Therefore, the objectives of this study were to measure the hard and soft tissue thicknesses in the median and paramedian regions of the palate, which are primarily favored for mini-implant insertion, and to evaluate the influences of age and sex on these thicknesses.…”
Section: Introductionmentioning
confidence: 99%
“…Because male and female patients have different growth patterns, the patient’s age and sex are important factors for determining the optimal implant placement site. Although several studies 8 , 9 have evaluated the hard tissue thickness of the palate, few have assessed the thickness of the soft tissue in the median and paramedian regions of the palate or investigated the influences of age and sex in terms of mini-implant insertion in these regions. Therefore, the objectives of this study were to measure the hard and soft tissue thicknesses in the median and paramedian regions of the palate, which are primarily favored for mini-implant insertion, and to evaluate the influences of age and sex on these thicknesses.…”
Section: Introductionmentioning
confidence: 99%
“…Another factor to be considered was the participant's age; most of the studies were conducted on adolescents or adults, whereas in this trial the patients were still young, and the palatal bone might not have been dense enough. 17 In summary, the results of this clinical trial revealed that both the CFPC and the MSPC appliances resulted in similar improvement in the amount of AOB closure that occurred as a result of the extrusion of the incisors. A few patients developed a lip-trap habit, which led to an increase in the amount of overjet as well as the amount of crowding in the mandibular anterior segment.…”
Section: Discussionmentioning
confidence: 64%
“…A recent study by Lyu et al [10] showed that the thicknesses of hard tissue and hard plus soft tissue at the first premolar plane were thickest among the four planes, followed by those at the second premolar molar, and second molar planes. In our design, the implant position is usually chosen between first premolar and first molar, 4-8 mm away from the midpalatal suture at the thickest part of palatal bone.…”
Section: Discussionmentioning
confidence: 96%
“…From the standpoint of mini-implant stability, the posterior two mini-implants are susceptible to loosening and failure in adolescent female patients due to inadequate palatal bone support. [10] us, hybrid bone-borne and toothborne palatal expanders with four palatal mini-implants are recommended for adolescents who require treatment with MARPE appliances.…”
Section: Discussionmentioning
confidence: 99%